Analysis of the modern school in times of pandemic in Ecuador - Carolina Armendariz; Alexandra Milla; Diego Yumisa; Diego Acosta (Universidad Ciencia y Tecnología, 2023)
This research examines how the COVID-19 pandemic has impacted education in Ecuador. The challenges in the implementation of online education are analyzed, and the solutions adopted to guarantee educational continuity amid the health crisis are explored. In addition, the pandemic has revealed gaps in access to technology and connectivity in the country, making equitable access to online education difficult for all students. Likewise, the emotional and psychological impact that the pandemic has had is addressed, and the importance of providing psychosocial support during these difficult times is highlighted. The main results show different factors associated with school dropout during the pandemic, including the lack of families' financial resources and the need for technological equipment to sustain connectivity between the student and the teacher.